Citizen Participation and Local Democracy in Zimbabwean Local Government System - A. F. Chikerema (International Organization of Scientific Research, 2023)
For the last twenty years, the concept of citizen participation and local democracy has largely been used in the local government discourse. These concepts are heavily related to the rights of citizens and democratic governance. Linking citizen participation to local government raises fundamental and normative questions about the nature of democracy and the skills and strategies for achieving it. This paper seeks to explore literature related to the dynamics and avenues of citizen participation and local democracy in Zimbabwean local government system. Factors which promote citizen participation and local democracy will be discussed including the issue of local government elections, participatory budget in local authorities, consultative forums, public hearings, existence of civil society organisations as well as the formal structures which exist within the local government institutions.